No stone unturned greek inscriptions and septuagint vocabulary - Aitken, J. K. 1968-2023 (Winona Lake Eisenbrauns, 2014)
Cover -- Title Page -- Copyright -- Contents -- Preface -- Abbreviations -- Chapter 1 The Current Study of Septuagint Vocabulary -- Chapter 2 Documentary Evidence in Biblical Lexicography -- Chapter 3 Working with Greek Inscriptions -- Chapter 4 New Words -- Chapter 5 Semantics, Grammar, and Register -- Chapter 6 Geographical Distribution -- Conclusions -- Appendix: Epigraphic Resources -- Bibliography -- Index of Modern Authors -- Index of Ancient Authors and Sources -- Index of Scripture -- Index of Inscriptions -- Index of Papyri -- Index of Words.
Description based on publisher supplied metadata and other sources
Keywords: Bible ; Old Testament ; Greek ; Septuagint ; Criticism, interpretation, etc; Greek language, Biblical; Electronic books